PELAYANAN JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) PADA RSUD. Dr. RM. PRATOMO BAGANSIAPI-API KABUPATEN ROKAN HILIR - Ilham Sulthany; Ernawaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
General Hospital Dr. RM. Pratomo Bagansiapi-api a central hospital in Rokan Hilir in general and people in particular Bagansiapi-api. The hospital is also home to the referral of patients for treatment using their own cost and user Jamkesmas and strategic enough mileage to 16 health centers in the area of Rokan Hilir. This study was conducted with several phenomena discovered by researchers in the field. That is a long process that tends to care for patients and the lack of a health fair attitude to patients who make their undifferentiated in terms of getting services. This study aims to determine a health care from hospitals Dr. RM. Pratomo Bagansiapi-api and to determine the factors that affect a health care from hospitals Dr. RM. Pratomo Bagansiapi-api. Descriptive qualitative research methods, data collection methods used observation and interviews. Theoretical concepts used are according to Agung Kurniawan who say that the administration of the service (serve) for a person or people who have an interest in him in accordance with the basic rules and procedures have been established, determined by several indicators, namely: Timeliness of service, accuracy of service, courteous and friendliness in service, ease of getting care, comfort in service, support service attributes, these indicators also to determine the factors that affect the implementation of the service. The results showed that a health services in hospitals Dr. RM. Pratomo not running optimally, because of the 6 indicators of overall service has not been achieved. For indicators of service timeliness, accuracy of service, courtesy and friendliness of the service, and the ease in getting the service is not maximized, while fatherly attributes of comfort and service support has been reached. Factors that affect service Jamkesmas at Hospital Dr. RM. Pratomo is the lack of medical personnel, procedures, and lack of long service tends polite and friendly attitude of employees towards the patient.Keywords: Services, Jamkesmas, Hospital